Characteristics and serology of pregnant women with cytomegalovirus immunoglobulin G seroconversion during pregnancy in Japan - Kyoko Shimada; Kuniaki Toriyabe; Asa Kitamura; Fumihiro Morikawa; Makoto Ikejiri; Toshio Minematsu; Haruna Nakamura; Shigeru Suga; Tomoaki Ikeda (Elsevier, 2021)
Objective: Investigate the characteristics and serology of pregnant women with cytomegalovirus (CMV) immunoglobulin (Ig)G seroconversion during pregnancy to understand the risk factors associated with primary CMV infection and the occurrence of fetal congenital CMV infection. Materials and methods: We retrospectively studied 3202 pregnant women who were CMV IgG-negative in early pregnancy and were retested for IgG in late pregnancy. Characteristics were compared between participants with and without IgG seroconversion, and serological parameters were compared between participants with and without fetal congenital CMV infection. Results: Twenty-six participants showed CMV IgG seroconversion and fifteen showed fetal congenital CMV infection. Seroconversion rates were significantly higher in teens (5.0%) than in older women (20s: 0.8%; 30s and over: 0.6%) (p < 0.001). Titers of CMV IgM at IgG seroconversion were higher in women without (median 8.66) than with (median 6.54) congenital infection (p = 0.045). The congenital infection rate was high when IgM titers at IgG seroconversion were low (47.1% with 4.00-12.00 titers and 100% with 1.21-3.99 IgM titers) (p = 0.048). Conclusions: Nulliparous pregnant teenagers have a high risk of CMV IgG seroconversion and the CMV IgM titer at IgG seroconversion may help predict the occurrence of fetal congenital CMV infection.